2016
DOI: 10.1039/c5nr09149g
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical TiO2/C nanocomposite monoliths with a robust scaffolding architecture, mesopore–macropore network and TiO2–C heterostructure for high-performance lithium ion batteries

Abstract: Engineering hierarchical structures of electrode materials is a powerful strategy for optimizing the electrochemical performance of an anode material for lithium-ion batteries (LIBs). Herein, we report the fabrication of hierarchical TiO2/C nanocomposite monoliths by mediated mineralization and carbonization using bacterial cellulose (BC) as a scaffolding template as well as a carbon source. TiO2/C has a robust scaffolding architecture, a mesopore-macropore network and TiO2-C heterostructure. TiO2/C-500, obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 53 publications
(33 reference statements)
2
18
0
Order By: Relevance
“…To further enhance the electrochemical performance of TiO 2 , TiO 2 /carbon composites have also been studied . Wang et al reported the synthesis of 3D hierarchical TiO 2 @C core–shell structure as anode material for LIBs .…”
Section: Hierarchical Tmos Based On Intercalation/deintercalation Reactionmentioning
confidence: 99%
“…To further enhance the electrochemical performance of TiO 2 , TiO 2 /carbon composites have also been studied . Wang et al reported the synthesis of 3D hierarchical TiO 2 @C core–shell structure as anode material for LIBs .…”
Section: Hierarchical Tmos Based On Intercalation/deintercalation Reactionmentioning
confidence: 99%
“…Employing various nanostructured mesoporous TiO 2 materials, especially for those with hierarchically porous structures as anodes for rechargeable LIBs, is popular [ 143 ]. For instance, hierarchically macro/mesoporous TiO 2 microparticles possess an excellent initial capacity of 235 and 202 mAh g −1 at 0.2 and 1 C, respectively [ 61 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Among the different kinds of TMOs, TiO 2 is an attractive material for LIBs owing to its natural abundance, low cost, and environmental benignancy ( Liu and Chen, 2014 , Liu et al., 2015a , Zhang et al., 2012 ). TiO 2 /C composite anode materials with various dimensions and structures have been fabricated, which include hierarchical TiO 2 /C nanocomposite monoliths ( Huang et al., 2016 ), ordered mesoporous TiO 2 /C nanocomposites ( Zeng et al., 2013 ), graphitic carbon conformal coating of mesoporous TiO 2 hollow spheres ( Liu et al., 2015b ), and mesoporous TiO 2 coating on flexible graphitized carbon ( Liu et al., 2016 ). However, all TiO 2 /C composites also suffer from severe structural collapse stemming from unstable TiO 2 -C interfaces.…”
Section: Introductionmentioning
confidence: 99%